N-acetylcysteine amide, a promising antidote for acetaminophen toxicity. (22nd January 2016) - Khayyat, Ahdab; Tobwala, Shakila; Hart, Marcia; Ercal, Nuran
Highlights: Glutathione depletion is an initiating event in the APAP-induced toxicity. N -acetylcysteineamide offers better protection than N -acetylcysteine in APAP-induced hepatotoxicity. N -acetylcysteineamide can be developed into a potential agent to treat the hepatotoxicity induced by APAP overdose. Mitochondrial dysfunction is a key event in APAP-induced hepatotoxicity. Abstract: Acetaminophen ( N -acetyl- p -aminophenol, APAP) is one of the most widely used over the counter antipyretic and analgesic medications. It is safe at therapeutic doses, but its overdose can result in severe hepatotoxicity, a leading cause of drug-induced acute liver failure in the USA. Depletion of glutathione (GSH) is one of the initiating steps in APAP-induced hepatotoxicity; therefore, one strategy for restricting organ damage is to restore GSH levels by using GSH prodrugs. N -acetylcysteine (NAC), a GSH precursor, is the only currently approved antidote for an acetaminophen overdose. Unfortunately, fairly high doses and longer treatment times are required due to its poor bioavailability. In addition, oral and I.V. administration of NAC in a hospital setting are laborious and costly. Therefore, we studied the protective effects of N -acetylcysteine amide (NACA), a novel antioxidant with higher bioavailability, and compared it with NAC in APAP-induced hepatotoxicity in C57BL/6 mice. Our results showed that NACA is better than NAC at a low dose (106 mg/kg) in preventing oxidative stress and protecting against APAP-induced damage. NACA significantly increased GSH levels and the GSH/GSSG ratio in the liver to 66.5% and 60.5% of the control, respectively; and it reduced the level of ALT by 30%. However, at the dose used, NAC was not effective in combating the oxidative stress induced by APAP. Thus, NACA appears to be better than NAC in reducing the oxidative stress induced by APAP. It would be of great value in the health care field to develop drugs like NACA as more effective and safer options for the prevention and therapeutic intervention in APAP-induced toxicity.